Mifepristone : Ongoing Role other Than an Abortion Pill - Laohareungpanya, Narumon (Journal of Basic and Applied Pharmacology, 2015)
Mifepristone is well known as an abortion pill that has been used since 1988. It acts as a strong competitive antagonist of progesterone that is an important hormone for maintaining gestation. Administration of mifepristone will lead to blastocyst detachment, increase sensitivity of myometrium to prostaglandin, ripen the cervix and result in pregnancy termination. Mifepristone also has other interesting benefits in treating many diseases that primarily affect women. It has been used to treat breast and ovarian cancer, tumor in brain, endometriosis and Cushing's syndrome. The legislation of mifepristone is expected to be an urgent problem in the future for Thai FDA committee. To permit this drug available in Thailand, its pharmacological actions must be concerned with moral and legal vision in Thai people together with the set up of protection process on drug abuse.